A Dyadic Perspective on Childhood Maltreatment for Women With Provoked Vestibulodynia and Their Partners: Associations With Pain and Sexual and Psychosocial Functioning. Issue 3 (24th March 2017) - Corsini-Munt, Serena; Bergeron, Sophie; Rosen, Natalie O.; Beaulieu, Noémie; Steben, Marc
Abstract : Childhood maltreatment is robustly associated with adult-onset vulvodynia, a common form of female genito-pelvic pain/penetration disorder. However, little is known about the impact of childhood maltreatment on current sexual, psychological, and relationship adaptation for couples with provoked vestibulodynia (PVD). This study examined the associations between childhood maltreatment and sexual and psychosocial functioning and pain in women with PVD, the most common subtype of vulvodynia, and their partners. A total of 49 couples ( M age women = 27.80, SD  = 6.05; M age men = 30.04; SD  = 6.48) with PVD completed the Childhood Trauma Questionnaire (CTQ), as well as measures of sexual functioning, couple satisfaction, and anxiety. Women also reported on their pain during intercourse. Analyses were guided by the actor–partner interdependence model. Women's higher reports of childhood maltreatment were associated with their lower sexual functioning and higher anxiety. Partners' higher reports of childhood maltreatment were associated with their lower sexual functioning, lower couple satisfaction, and higher anxiety, as well as women's lower couple satisfaction and higher anxiety. Both women's and partners' higher reports of childhood maltreatment were associated with higher affective pain for women. Findings suggest childhood maltreatment experienced by women with PVD and their partners should be considered as part of treatment planning.